Adjuvant anti-PD-1 therapy improves melanoma-specific survival in stage IIIC-IV melanoma patients with high tumor mutation burden and BRAF V600 mutation - Forschner, Julia; Huynh, Julia; Schroeder, Christopher; Armeanu-Ebinger, Sorin; Seibel-Kelemen, Olga; Gschwind, Axel; Bonzheim, Irina; Eigentler, Thomas K.; Amaral, Teresa; Ossowski, Stephan; Flatz, Lukas; Garbe, Claus; et al. (Frontiers in Oncology, 2025)
Immune checkpoint inhibitors (ICI) have significantly improved melanoma-specific survival (MSS), particularly in patients with tumors with a high tumor mutational burden (TMB) or BRAF mutation. In the adjuvant setting, ICIs significantly improve relapse-free survival (RFS), but data on MSS are still lacking. Tissue samples from 83 patients with stage IIIC/D/IV melanoma who started adjuvant ICI between March 2018 and September 2019 were examined using a 700 gene panel. TMB and BRAF V600E/K mutation status were analyzed to determine their potential influence on RFS and MSS. TMB levels ≥ 20 Var/Mb were classified as TMB high, corresponding to the top 20% TMB levels in the cohort. RFS and MSS were significantly improved in patients whose tumors had high TMB levels and BRAF V600E/K mutation (p<0.001 and p=0.002, respectively). Patients with BRAF-mutated tumors and high TMB seem to benefit particularly from adjuvant ICI.